Обґрунтування вибору робочих концентрацій молочної кислоти для електрохімічного синтезу надмолочної кислоти - Водолажченко, Сергій Олександрович; Дерібо, Світлана Германівна; Шахин, Иссам Х.; Павлов, Богдан Володимирович (Київський національний університет технологій та дизайну, 2019)
Disadvantages of traditional methods of peroxolactic acid synthesis stimulate the search of new technological solutions which meet the requirements of modern production. A high-purity peroxolactic acid may be produced by electrochemical method. The aim of this work was to determine the nature of the substances involved in the combined processes on the platinum anode in a wide range of concentrations of lactic acid and the potential of the anode. The choice of staging of electrochemical synthesis of peroxolactic acid is substantiated. The E − pH diagram of the CH3CH(OH)COOH − Н2О system is constructed. It has been shown that the peroxo group can be formed by both the oxidation of the acetate ion at the anode-electrolyte interface and the action of the peroxo compound synthesized on the anode surface on lactic acid molecule. Anodic processes in the solutions of lactic acid in the con centration range of 0,5…8 mol/dm3 have been investigated by the voltammetry method on a platinum electrode. It has been shown that increasing the lactic acid concentration up to 6 mol/dm3 shifts the equilibrium potential on the platinum electrode in the positive direction which is caused by the increasing adsorption of organic compounds. It has been established that the working concentration of lactic acid at which the maximum current effi- ciency are in the range of 3…4 mol/dm3 .
Rationale for the Choice of Lactic Acid Working Concentration for Elec-trochemical Synthesis of Sulphurous Acid
Keywords: lactic acid; peroxolactic acid; electrochemical synthesis; platinum anode; combined processes; молочна кислота; пероксомолочна кислота; електрохімічний синтез; платиновий анод; комбіновані процеси